Evaluation of postoperative pain management strategies in maxillofacial surgery patients - Bukhsh, Ayman T.; Alnakhli, Sawsan H.; Alzahrani, Osama S.; Barakat, Omar M.; Muwainea, Aljazi M.; Alraddadi, Ibrahim S.; Alsaleh, Abdulaziz A.; Albishri, Nawaf A.; Hakami, Lamia S.; Almarshadi, Ruqayyah H.; Alnujaidi, Ahmed M. (International Journal Of Community Medicine And Public Health, 2024)
Evaluating postoperative pain management strategies in maxillofacial surgery is essential for optimizing patient outcomes and satisfaction. This review assesses various pain management approaches, emphasizing the importance of a multimodal strategy. Effectiveness is measured using standardized pain scales such as the visual analog scale (VAS) and numeric rating scale (NRS), along with evaluating functional recovery indicators like chewing, swallowing, and speaking. Safety considerations focus on monitoring adverse effects from analgesics, ensuring proper wound healing, and minimizing infection risks. Patient satisfaction is gauged through direct feedback on pain management experiences and adherence to prescribed regimens. Cost-effectiveness is analyzed by evaluating resource utilization, including hospital stay duration, additional medical interventions, and medication costs. Studies indicate that comprehensive pain management bundles, although initially more expensive, can lead to long-term cost savings and improved patient outcomes. Implementing a patient-centred, multidisciplinary approach that includes both pharmacological and non-pharmacological methods is crucial for effective pain management in maxillofacial surgery.